(untitled) (Global Journal of Management and Business Research, 2024)
The purpose of this article was to propose various training programs for the development of owners and managers of private Greek enterprises The author of this article has been examining analyzing evaluating and critiquing the state of management practices in private Greek enterprises since 1971 He has written and published a dissertation on private Greek enterprises for his doctoral degree from the Aristotelian University of Thessaloniki and a number of peer-reviewed articles on the same topic the last of which was published in 2023 The absence of effective and efficient training of the managers and owners of private Greek enterprises was mentioned in each of the above-cited publications however no suggestions for training were presented because training was not a topic of discussion in any of the above-cited publications